Career Decision Making, Stress, and Its Association with Emotional Intelligence among Medical Undergraduates at HITEC-IMS Taxila Cantt: Career Decision Making, Stress, and Its Association with Emotional Intelligence - Afzal, Asifa; Rafaqat, Nida; Siddiqui, Raima; Raza, Mohsin; Riaz, Mah; Zulqarnain, Muhammad (Pakistan Journal of Health Sciences, 2026)
Medical students are exposed to a wide range of medical specialties during their medical school journey. The most crucial decision at that time is the choice of a career. Objectives: To assess the level of career decision-making stress and determine its association with emotional intelligence among medical undergraduates of HITEC‑IMS, Taxila Cantt. Methods: A cross-sectional study was conducted among HITEC‑IMS medical undergraduates from June to October 2025 via stratified random sampling. Data were collected through a structured questionnaire, covering sociodemographic variables, the Career Decision Difficulty Questionnaire (CDDQ), and the Brief Emotional Intelligence Scale 10 (BEIS-10). SPSS version 26.0 was used for analysis. For continuous variables, mean and standard deviation, and for categorical variables, frequency and percentages were calculated. Association between two variables was seen using Chi Square test and Spearman Correlation. Results: 48.6% individuals experienced moderate career decision stress, with most (62.8%) struggling with a lack of readiness. The majority (85.3%) had average EI, while 14.7% scored below average. Overall, CDDQ showed a significant association with study year (p=0.004), mother and father occupation (p=0.021 and p=0.010), lack of readiness to number of siblings (p=0.033), and year of study with lack of information(p-0.043). Career‑decision stress showed a significant inverse correlation with emotional intelligence (p = –0.404, p<0.001). Conclusions: Almost half of the students face moderate stress in career decision-making, but those with higher Emotional Intelligence tend to experience less of it. Strengthening EI and implementing structured career counselling can be effective strategies to alleviate stress and support more informed, confident career choices.